Mid-term follow-up of renal artery reimplant in open surgical repair for abdominal aortic aneurysm with a crossed-fused renal ectopia - Diego Soto V, MD; Gabriel Cassorla J, MD; Francisco Goyenechea M, MD; Cristian Marín O, MD; Sebastián Morales Z, MD; Gabriel Seguel S, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Crossed-fused renal ectopia is an uncommon congenital condition, and its association with abdominal aortic aneurysm can present a complex surgical scenario. We present a case of a 71-year-old male with abdominal aortic aneurysm and crossed-fused renal ectopia who underwent open surgical repair with renal artery reimplantation, using mannitol infusion and cold crystalloid perfusion for renal protection. Postoperatively, after transient creatinine rise, renal function normalized without dialysis. At 24 months follow-up, the reimplanted renal artery remains patent with normal renal function. This case illustrates open surgical repair’s effectiveness in addressing complex vascular anatomy, ensuring durable outcomes, and preserving vessel patency and renal function.